Job Satisfaction in the Context of High-Performance Work Systems and Work–Life Balance: The Mediating Role of Work Overload and Lessons for Educational Management - Netania Emilisa; Nadira Feliza Aulia (Journal of Educational Management Research, 2026)
This study aims to examine the effects of High-Performance Work Systems (HPWS) and work–life balance on job satisfaction, with work overload as a mediating variable. The research was conducted among employees in the fast-food industry as an empirical context to generate broader insights for educational management. A quantitative approach was employed using a survey method, with data were collected through online questionnaires distributed via Google Forms. A total of 150 respondents were selected using purposive sampling. Data analysis involved descriptive statistics and mediation analysis to investigate the relationships among variables. The results indicate that work overload significantly mediates the relationship between HPWS and job satisfaction, suggesting that the implementation of high-performance work practices influences job satisfaction through workload intensity. However, work overload does not mediate the relationship between work–life balance and job satisfaction, indicating that work–life balance affects job satisfaction through alternative pathways beyond workload pressure. These findings imply that educational institutions should carefully design high-performance management systems while maintaining balanced workload structures to enhance job satisfaction among teachers and educational personnel. The study underscores the strategic importance of workload management in supporting sustainable human resource management within educational organizations.